Organization of Medical Assistance in Poland for Ukrainian Citizens During the Russia-Ukraine War - Fatyga, Edyta; Dzięgielewska-Gęsiak, Sylwia; Muc-Wierzgoń, Małgorzata (Frontiers in Public Health, 2022)
From 24 February 2022 to 29 March 2022, Poland has taken 2,377,000 refugees fleeing Russia's invasion of Ukraine. They are mostly women, children, and the elderly. In this article, we present all activities and types of medical resources provided and organized in Poland for refugees from the first days of the conflict. Information has been compiled from the data available on the Polish Ministry of Health, other governmental and non-governmental organizations, foundations, and medical societies.